Contributors to negative biopsychosocial health or performance outcomes in rugby players (CoNBO): a systematic review and Delphi study protocol. Issue 4 (11th October 2022) - McCormack, Sam; Till, Kevin; Wenlock, Jessica; Whitehead, Sarah; Stokes, Keith A; Bitcon, Mark; Brown, James; Cross, Matt; Davies, Phil; Falvey, Éanna C; Flahive, Sharron; Gardner, Andrew; et al.
Abstract : The importance of contributors that can result in negative player outcomes in sport and the feasibility and barriers to modifying these to optimise player health and well-being have yet to be established. Within rugby codes (rugby league, rugby union and rugby sevens), within male and female cohorts across playing levels (full-time senior, part-time senior, age grade), this project aims to develop a consensus on co ntributors to n egative b iopsychosocial o utcomes in rugby players (known as the CoNBO study) and establish stakeholder perceived importance of the identified contributors and barriers to their management. This project will consist of three parts; part 1: a systematic review, part 2: a three-round expert Delphi study and part 3: stakeholder rating of feasibility and barriers to management. Within part 1, systematic searches of electronic databases (PubMed, Scopus, MEDLINE, SPORTDiscus, CINAHL) will be performed. The systematic review protocol is registered with PROSPERO. Studies will be searched to identify physical, psychological and/or social factors resulting in negative player outcomes in rugby. Part 2 will consist of a three-round expert Delphi consensus study to establish additional physical, psychological and/or social factors that result in negative player outcomes in rugby and their importance. In part 3, stakeholders (eg, coaches, chief executive officers and players) will provide perceptions of the feasibility and barriers to modifying the identified factors within their setting. On completion, several manuscripts will be submitted for publication in peer-reviewed journals. The findings of this project have worldwide relevance for stakeholders in the rugby codes. PROSPERO registration number CRD42022346751.